Fear of missing out on social media: implications for private and professional lives - Luukela-Tandon, Anushree (fi=Turun yliopisto|en=University of Turku|, 2023)
The “dark side” of social media use is a topic of vivid discourse in academia and mass media. Within this discourse, various negative effects, such as social media fatigue, addictive or compulsive use, and social media use-related sleep problems have garnered attention. The Fear of Missing Out (FoMO) is a particular dark side of social media phenomenon that has significant implications for diverse segments of social media users. In the past decade, since the operationalization of FoMO, scholars, especially those researching social media, have made continuing progress in understanding FoMO’s conceptual foundations as well as the capacities in which FoMO can influence the well-being of social media users. Despite the growing scholarly interest, research on FoMO is fragmented and features significant knowledge gaps, such as a limited understanding of its consequences and a lack of focus in prior studies beyond young adults and teenagers as a respondent group. These gaps need to be addressed as myriad mass media reports and academic studies have linked social media users’ experience of FoMO with indicators of diminished well-being, which in turn has implications for these users’ personal and professional lives. The aim of this dissertation is to investigate how FoMO, as a context-specific psychological trigger, predicates users’ experience of phenomena associated with the dark side of social media such as social media fatigue, compulsive social media use, and social media stalking. It further investigates the influence of such FoMOdriven experiences on individual users’ professional and personal lives. This dissertation examines FoMO within the social media environment and investigates theoretically grounded frameworks that illustrate the pathways through which FoMO may lead to negative consequences. The dissertation comprises five articles: one systematic literature review (Article I) and four quantitative studies (Articles II–V) developed based on the review findings. Following a systematic review of 58 empirical publications on FoMO, Article I provides foundational knowledge on FoMO’s known antecedents and consequences, indirect influencers (moderators and mediators), study contexts, conceptualization, and operationalization. The results are used to present an overarching framework and five key propositions for advancing research on FoMO. The findings of Articles II and III provide new insights into FoMO’s influence on the personal well-being of social media users. Discerning significant links between FoMO and the compulsive use of social media, online social comparison, social media stalking, and disruptions in sleep hygiene (i.e., sleep-related habits and routines), these articles argue that FoMO could culminate in social media users’ experiences of problematic sleep and social media fatigue. The findings also show that FoMO may have an amplification effect on the users’ dark side of social media experiences on these platforms, albeit through different manifestations among young adults and working professionals. Articles IV and V focus on FoMO-driven social media use in the workplace and the subsequent consequences. In doing so, this research empirically investigates employees, who are a relatively less-studied demographic in the FoMO research compared to young adults. The findings show that FoMO has the capacity to predict diminished work performance, work procrastination, phubbing (the problematic use of smartphones during social or workplace interactions), workplace exhaustion, and work incivility. Further, these articles show that individual characteristics, such as regulatory focus and social media envy, play an important role in users’ experiences of negative consequences. Collectively, the findings of this dissertation provide novel insights into the mechanisms through which FoMO can trigger the problematic use of technological platforms, such as social media and smartphones, and users’ engagement in activities that are intrinsically linked with the dark side of social media. The dissertation suggests that FoMO and the dark side of social media phenomena may indeed have a cyclical relationship wherein one may trigger another, causing a vicious loop. In addition to advancing the understanding of ways in which FoMO can negatively influence an individual’s life, the findings hint at its potential to indirectly, but positively, benefit individual performance in the workplace. In doing so, the dissertation creates new knowledge on the dual effects of FoMO. Cumulatively, the findings of this dissertation, particularly Article I, provide several avenues that scholars can pursue to further advance the frontier of knowledge on FoMO in particular and the dark side of social media in general. KEYWORDS: Fear of missing out, dark side of social media, compulsive use, phubbing, problematic sleep, work performance

Sosiaalisen median ei-toivotut vaikutukset (sosiaalisen median pimeä puoli) palvelujen käyttäjille ovat viime vuosina olleet vilkkaan julkisen keskustelun ja akateemisen tutkimuksen kohteena. Aihepiirin tutkimus on tarkastellut mm. käyttäjien väsymystä sosiaalisen mediaan, riippuvuutta sosiaalista mediaa kohtaan, sosiaalisen median pakonomaista käyttöä, sekä sosiaalisen median käytön vaikutusta uneen. Paitsi jäämisen pelko (Fear of Missing Out, FoMO) on ilmiö sosiaalisen median pimeiden puolin kentässä, jolla on havaittu merkittäviä, tyypillisesti kielteisiä vaikutuksia palvelujen käyttäjiin. Lisääntyneestä tutkimuksesta huolimatta ymmärrys FoMO:sta on pirstaloitunutta. Tutkimuskirjallisuus on korostanut erityisesti tarvetta FoMo:n käsitteellis-teoreettisen taustan ymmärryksen vahvistamiselle ja tarvetta ymmärtää FoMO:n vaikutuksia sosiaalisen median palvelujen käyttäjien hyvinvoinnille. Tämän väitöstutkimuksen tavoitteena on osaltaan täyttää em. aukkoja aiemmassa tutkimuksessa tutkimalla FoMO:a kontekstisidonnaisena psykologisena laukaisevana tekijänä, jolla on vaikutuksia sosiaalisen median käyttäjiin niin yksityis- kuin työelämässäkin. Väitöskirja koostuu viidestä artikkelista: yhdestä systemaattisesta kirjallisuuskatsauksesta (Artikkeli I) ja neljästä kvantitatiivisesta kyselytutkimuksesta (Artikkelit II–V), jotka on kehitetty kirjallisuuskatsauksen tulosten perusteella. Artikkeli I perustuu 58 empiiriseen julkaisuun FoMO:sta ja tarjoaa perustiedot FoMO:on vaikuttavista tekijöistä ja seurauksista, epäsuorista vaikuttajista (moderaattorit ja välittävät muuttujat), tutkimuskonteksteista, käsitteellistämisestä ja operationalisoinnista. Tuloksia käytetään esittämään tutkimuksellinen viitekehys ja viisi keskeistä suuntaa FoMO:n tutkimuksen edistämiseksi. Artikkelien II ja III tulokset tarjoavat uusia näkökulmia FoMO:n vaikutukseen sosiaalisen median käyttäjien henkilökohtaiseen hyvinvointiin. Artikkeleissa havaitaan merkittäviä yhteyksiä FoMO:n ja sosiaalisen median pakonomaisen käytön, verkossa tapahtuvan sosiaalisen vertailun, sosiaalisessa mediassa tapahtuvan vainoamisen (stalking) ja unihygienian häiriöiden (eli unen laatuun vaikuttavien tapojen ja rutiinien) välillä. Artikkelit osoittavat, että FoMO voi johtaa sosiaalisen median käyttäjien kokemaan ongelmalliseen uneen ja väsymykseen sosiaalista mediaa kohtaan. Artikkelit IV ja V keskittyvät FoMO:n ajamaan sosiaalisen median käyttöön työpaikalla ja siihen liittyviin seurauksiin. Tulokset osoittavat, että FoMO voi ennustaa heikentynyttä työsuoritusta, työn viivyttelyä, puhelinten liiallista käyttöä sosiaalisissa tilanteissa tai työympäristössä (phubbing), työuupumusta ja epäkohteliasta käyttäytymistä työpaikalla. Lisäksi nämä artikkelit osoittivat yksilön ominaisuuksien tärkeän roolin käyttäjien kokemuksissa näistä negatiivisista seurauksista. Kokonaisuutena väitöstutkimukseen sisällytettyjen artikkeleiden tulokset tarjoavat uutta tietoa FoMO: on vaikuttavista tekijöitä ja sen seurauksista niin ihmisten yksityiselämässä kuin työkontekstissakin. Tulokset tarjoavat viitteitä FoMO:n ja sosiaalisen median pimeän puolen välisestä toisiaan vahvistavasta syklisestä suhteesta. Tulokset tarjoavat myös, osin yllättävästi, viitteitä, että paremmin tunnettujen kielteisten vaikutustensa lisäksi FoMO:lla voi olla myös positiivisia vaikutuksia yksilön suorituskykyyn työpaikalla. Väitöstutkimus tarjoaa kattavan viitekehyksen, jota erityisesti FoMO:n ja yleisemmin sosiaalisen median pimeän puolen tutkimuksessa. ASIASANAT: Paitsi jäämisen pelko, sosiaalisen median pimeä puoli, pakonomainen käyttö, phubbing, uniongelmat, suorituskyky töissä